2016
DOI: 10.3354/esr00723
|View full text |Cite
|
Sign up to set email alerts
|

Photo-ID as a tool for studying and monitoring the endangered Saimaa ringed seal

Abstract: Photo-identification (photo-ID) with camera traps was examined as a non-invasive method for studying and monitoring the endangered Saimaa ringed seal Phoca hispida saimensis. An average of 51 game cameras were set up at shoreline haul-out sites in central Lake Saimaa during the moulting seasons in each of the years from 2010 to 2014. Individuals were identified from their lifelong unique lateral fur patterns. A total of 220 000 digital images of seals were obtained from these game cameras and from digital came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…As the Saimaa ringed seal is known for its high degree of site fidelity (e.g., [24]), we assumed that the individual seals use the same home ranges year to year; therefore, neighbors could be investigated even when tracked in different study years. Furthermore, a recent photo-identification study (see [44]) confirmed that all neighboring seals were alive throughout the study period. It may be possible that there were other non-tagged seals in the same areas; therefore, the placenta findings were examined with respect to the breeding density independent from the instrumentation.…”
Section: Methodsmentioning
confidence: 68%
See 3 more Smart Citations
“…As the Saimaa ringed seal is known for its high degree of site fidelity (e.g., [24]), we assumed that the individual seals use the same home ranges year to year; therefore, neighbors could be investigated even when tracked in different study years. Furthermore, a recent photo-identification study (see [44]) confirmed that all neighboring seals were alive throughout the study period. It may be possible that there were other non-tagged seals in the same areas; therefore, the placenta findings were examined with respect to the breeding density independent from the instrumentation.…”
Section: Methodsmentioning
confidence: 68%
“…The function of female territoriality during the breeding season has been assumed to be related to resource defense [64]. It is well known that Saimaa ringed seals exhibit high site fidelity [4, 19, 20, 44] and that females are especially philopatric [65]. Therefore, we suggest that a lair site with a sufficient annual snow cover for birth lair creation could be a resource worth of interannual defense by the ringed seal females.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…From the early days of taxonomy, species descriptions have been accompanied by various types of visual support that are vital to convey information about the morphology and character states used to distinguish species (Akkari et al 2015, García-Melo et al 2018. Currently, the use of digital images in taxonomy has focused on photo-identification methods (Dala-Corte et al 2016) in studies of large vertebrates (Bertulli et al 2015;Koivuniemi et al 2016;Treilibs et al 2016), amphibians (Sannolo et al 2016), lizards (Sreekar et al 2013;Knox et al 2016), invertebrates (Caci et al 2013, Chim & Tan 2012, fishes (Speed et al 2007;Dala-Corte et al 2016), and bats (Rydell & Russo 2014). Few works, however, have attempted to standardize protocols for field photography to provide images that are taxonomically informative for scientific publications and aesthetically attractive for disseminating knowledge and promoting biodiversity conservation to a broader constituency.…”
Section: Introductionmentioning
confidence: 99%